Partial Edentulousness in Patients Visiting the Dental Out-Patient Department of Gandaki Medical College, Pokhara, Nepal - Bhandari, A.; Manandhar, A.; Manandhar, P. (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Partial edentulousness is a dental arch in which one or more but not all natural teeth are missing due to dental caries, periodontal problems, trauma etc. It causes difficulty in chewing food, alteration of speech and unpleasant esthetics which adversely affect the general health and quality of life.Methods: This study was conducted in the Department of Prosthodontics, College of Dental Surgery, Gandaki Medical College, Pokhara from November 2017 to March 2018. All patients above the age of 15 years presenting with partial loss of dentition and willing to give informed consent were included in the study. Data regarding age, gender, missing teeth, cause of permanent tooth loss and denture status were collected from 342 patients.Results: The most common cause of permanent tooth loss was dental caries (58.2%) followed by periodontal (18.1%), dental caries and periodontal (9.4%), trauma (7.9%), dental caries and trauma (2.9%), periodontal and trauma (2.3%) and others (1.2%).The distribution of partially edentulous areas in maxillary arch (35.7%), mandibular arch (45.9%) and both arches (18.4%).The most common type of partial edentulism was found to be Kennedy’s class III followed by class II, class I and class IV in both the arches.Conclusion: The most common cause of permanent tooth loss was dental caries. Mandibular arch was more affected than the maxillary arch. The most common type of partial edentulism was Kennedy’s class III.